The effect of consuming caffeine before late afternoon/evening training or competition on sleep: a systematic review with meta-analysis - Kocak, A.; Georgousopoulou, E.; Knight-Agarwal, C. R.; Matthews, R.; Minehan, M. (Sports, 2025)
Many athletes consume caffeine before late afternoon/evening training sessions or competition, yet the impact on subsequent sleep remains unclear. This systematic review with meta-analysis examined the effects of late afternoon/evening caffeine consumption on sleep in athletes. Ten studies (n = 128 athletes) involving randomized controlled trials and quasi-experimental designs were included if caffeine was consumed prior to late afternoon/evening training and subsequent sleep was measured. Meta-analysis followed PRISMA guidelines with risk of bias assessed using RoB-2 and ROBINS-I tools. Meta-analysis of randomized controlled trials revealed a small reduction in sleep efficiency with evening caffeine consumption: mean difference -4.87%, 95% CI -7.45 to -2.29, p = 0.04, though this effect was not robust in leave-one-out sensitivity analyses. Total sleep time showed a non-significant trend toward reduction: mean difference -32.47 min, 95% CI -69.93 to 4.99, p = 0.08, I2 = 0%. Athletes consistently reported substantial subjective sleep impairment following evening caffeine intake (3-6 mg/kg BM), creating a pronounced objective-subjective disconnect. The most notable finding is that athletes consistently perceive substantial sleep disruption despite inconsistent objective changes, highlighting the importance of subjective sleep experience in athletic populations. These findings should be interpreted cautiously given the small number of studies and predominance of male participants, limiting generalisability.